PEMBERDAYAAN LARVA (Maggot black soldier fly) DALAM MENGOLAH SAMPAH ORGANIK DI DAERAH RW 12 & RW 04 KELURAHAN CITEUREUP CIMAHI UTARA - Iis Kurniati; Asep Dermawan; Nina Marliana (Poltekkes Kemenkes Bandung, 2022)
Garbage is a serious problem and has not been utilized optimally. Therefore, it is necessary to find a solution so that organic waste can be minimized and become more useful. One of the efforts that can be applied in the Rw 12 and Rw 04 areas, Citeureup Village, North Cimahi, is bioconversion using larvae (Maggot black soldier fly). BSF larvae with their ability to degrade organic waste are used to convert organic matter so that they have economic potential. Garbage is the residual waste from a product or item that is no longer used, but can still be recycled into valuable goods. Meanwhile, organic waste is waste that comes from the rest of living things that can easily decompose naturally without human intervention. Organic waste can be regarded as environmentally friendly waste and even waste can be reprocessed into something useful if managed properly. However, if this organic waste is not managed properly, it will cause disease and an unpleasant odor which is the result of the rapid decomposition of organic waste. The method offered is technology transfer through counseling, training and mentoring. The expected result of this research is an increase in the knowledge, skills of partners about the bioconversion of waste using BSF larvae, as well as obtaining other additional products in the form of organic vegetables obtained from cultivation using biodegradable waste commonly called maggot (kasgot) and organic catfish that are fed using maggot, so this activity can help in efforts to improve family nutrition.